WANITA “AHMADI” DALAM NOVEL MARYAM: KAJIAN PSIKOLOGI B.F. SKINNER - Muhammad Hambali; Saharudin Saharudin; Muh. Khairussibyan (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2023)
This study aims to examine the psychology of the main character in the novel Maryam by Okky Madasari in order to determine the response stimulus experienced by the main character and other characters with the literary psychology approach of B.F. Skinner. The data source of this research is the novel Maryam by Okky Madasari. The results showed that the psychology of Maryam's character as a woman